2004
DOI: 10.1002/macp.200300174
|View full text |Cite
|
Sign up to set email alerts
|

Swelling, Elasticity and Spatial Inhomogeneity of Poly(N,N‐dimethylacrylamide) Hydrogels Formed at Various Polymer Concentrations

Abstract: Summary: The equilibrium swelling degree, modulus of elasticity and the spatial inhomogeneity of poly(N,N‐dimethylacrylamide) (PDMAAm) hydrogels were investigated over the entire range of the initial monomer concentration. The degree of dilution of the networks after their preparation was denoted by ν, the volume fraction of crosslinked polymer after the gel preparation. The linear swelling ratio of the gels increased linearly with increasing ν. Depending on the value of ν, three different gel regimes were obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 46 publications
5
75
0
Order By: Relevance
“…For the following calculations, we set A ¼ 1. Further, assuming the conversion of the monomer to the crosslinked polymer is complete, using the polymer densities 1.35 g/ml for both PAAm and PNIPA [14], 1.21 g/ml for PDMA [16], n 0 2 was calculated as 0.037, 0.037, and 0.041, respectively. The polymer volume fraction relates to V rel by n 2 ¼ n 0 2 =V rel .…”
Section: Resultsmentioning
confidence: 99%
“…For the following calculations, we set A ¼ 1. Further, assuming the conversion of the monomer to the crosslinked polymer is complete, using the polymer densities 1.35 g/ml for both PAAm and PNIPA [14], 1.21 g/ml for PDMA [16], n 0 2 was calculated as 0.037, 0.037, and 0.041, respectively. The polymer volume fraction relates to V rel by n 2 ¼ n 0 2 =V rel .…”
Section: Resultsmentioning
confidence: 99%
“…Gundogan et al showed that increasing monomer concentration caused the polymer chains to entangle so that the network formed in a concentrated solution can swell less than that formed in a dilute solution. [22] Therefore, the swelling ratios of the 22C0 cryogels are lower than those of the 22C45 cryogels at the same time interval.…”
Section: Swelling Kineticsmentioning
confidence: 92%
“…V 2 , the volume fraction of cross-linked polymer, was determined by the following equation. 35 V2=false(1+false(qf1false)ρ/dfalse)1where q f is the mass of the swollen hydrogel divided by the mass of the freeze-dried hydrogel. The density of the solvent (alpha minimum essential media), d , is assumed to be 0.997 g/mL.…”
Section: Experimental Methodsmentioning
confidence: 99%